2020
DOI: 10.21608/edj.2020.24160.1034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surface Roughness and Microbial Biofilm Adhesion of Different Orthodontic Arch-wires

Abstract: Objectives: To assess the capability of different orthodontic arch-wires to retain oral biofilm and to correlate the adhesion to surface roughness of the wires. Methods: Four types of orthodontic arch-wires were used for the study, Nickel-titanium (NiTi), Copper nickel-titanium (Cu-NiTi) , Beta Titanium (TMA) & Beta III Titanium (CNA) new arch wires and 4 weeks after intraoral usage, were examined for Surface roughness (SR) using an atomic force microscope (AFM). Adhesion of Streptococcus mutans (MS), Staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In relation to orthodontic brackets, studies have been conducted which have shown various bacterial adhesion depending on the type of bracket (conventional/self-ligaturing) and the material from which it is made [ 11 , 30 , 31 , 32 ]. Furthermore, there have been studies on orthodontic wires that have proven a link between biofilm formation and the degree of roughness [ 27 , 33 , 34 , 35 ]. Tawfik et al proved that there is a strong, linear correlation between the roughness of orthodontic archwires and the formation of bacterial biofilm [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to orthodontic brackets, studies have been conducted which have shown various bacterial adhesion depending on the type of bracket (conventional/self-ligaturing) and the material from which it is made [ 11 , 30 , 31 , 32 ]. Furthermore, there have been studies on orthodontic wires that have proven a link between biofilm formation and the degree of roughness [ 27 , 33 , 34 , 35 ]. Tawfik et al proved that there is a strong, linear correlation between the roughness of orthodontic archwires and the formation of bacterial biofilm [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there have been studies on orthodontic wires that have proven a link between biofilm formation and the degree of roughness [ 27 , 33 , 34 , 35 ]. Tawfik et al proved that there is a strong, linear correlation between the roughness of orthodontic archwires and the formation of bacterial biofilm [ 35 ]. There are no such studies on brackets, however, one should expect a similar correlation for metal brackets.…”
Section: Discussionmentioning
confidence: 99%
“…20 The finding of this study agreed with other studies that also find the TMA wires had the highest surface roughness. [21][22][23] While, nickel free stainless steel wires showed a very low values of their roughness average in the all conditions inspite of the statistical difference was only in the as received condition. This give the wire a superiority as working wire in the sliding mechanic of the second stage of the orthodontic treatment, as its smooth surface will enhance the performance of the appliance, and hence, the quality of the orthodontic treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Orthodontic stainless steel and NiTi archwires are used fundamentally during the course of orthodontic treatment with fxed appliances and are considered a common site for the development of microbial plaque [40,41]. Several studies evaluate the microbial adhesions to diferent orthodontic archwires following intraoral wearing of the appliances that concluded that bioflm adherence increased in the archwires with time and the surface roughness of archwires was positively correlated with bioflm adherence [42][43][44].…”
Section: Discussionmentioning
confidence: 99%